KINERJA UNIT USAHA KEDELAI DENGAN MENGGUNAKAN METODE BALANCED SCORECARD: (Studi Kasus Pada Koperasi Produsen Tempe Tahu Indonesia Kabupaten Kuningan) - hakim, abdul; Sulviani, Agustine; Nur Hamidah, Regina Winny; Supriyadi R, Ery (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2023)
This study aims to determine the performance of the soybean business unit of the Indonesian Tempe and Tofu Producers Cooperative in Kuningan Regency using the balanced scorecard method. This research is a case study. The research informants were 3 administrators, 3 supervisors and managers, 8 employees, and 62 members of the Indonesian Tempe and Tofu Producers Cooperative, Kuningan Regency. The object of this research is the soybean business unit of the Indonesian Tempe and Tofu Producers Cooperative in Kuningan Regency which is analyzed using the Balanced Scorecard from a financial perspective, a customer or member perspective, an internal business perspective, and a learning and growth perspective. The results of the research on performance achievement in the soybean business unit of the Indonesian Tempe and Tofu Producers Cooperative in Kuningan Regency show that the financial perspective is in the negative criteria, the customer perspective has good criteria, the internal business perspective is in very good criteria, the learning and growth perspective is quite good.